A scrap-tolerant alloying concept based on high entropy alloys. (November 2020) - Barnett, M.R.; Senadeera, M.; Fabijanic, D.; Shamlaye, K.F.; Joseph, J.; Kada, S.R.; Rana, S.; Gupta, S.; Venkatesh, S.
Abstract: The present article advances the idea of compositional flexibility. The intent is to provide an avenue for value creation from waste alloys in cases where costs of separating co-mingled alloy flows are prohibitively high. A compositionally flexible alloy has the potential to be produced solely from varying and intermingled flows of end-of-life alloys. While the alloy composition may vary from day-to-day or from heat-to-heat, the intent is that it will still satisfy base performance targets. Using FeNiCr based high entropy alloys as inspiration, we exploited Bayesian Optimization to define a number of example compositionally complex alloys that display strengths within specified limits (150-250 MPa, 200-350 MPa and 300-350 MPa). The concept was motivated by the surprising number of high entropy alloys reported in the literature that display a similarity of properties despite their wide dispersion of composition. We propose a simple measure of compositional flexibility by combining the ranges over which each elemental addition is permitted to vary and suggest methods of alloy specification. A series of 68 prototype compositions were produced and characterized to demonstrate the concept and approach. We show that our model alloys could conceivably be produced using multiple different combinations of existing Ni alloys in combination with 316 stainless steel. Our hope is that the concept will find application to facilitate alloy recovery where it might not otherwise be feasible.